2017
DOI: 10.1167/iovs.16-20273
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Reach-to-Grasp and Transport-to-Place Performance in Participants With Age-Related Macular Degeneration and Glaucoma

Abstract: Citation: Pardhan S, Scarfe A, Bourne R, Timmis M. A comparison of reachto-grasp and transport-to-place performance in participants with age-related macular degeneration and glaucoma. Invest Ophthalmol Vis Sci. 2017;58:156058: -156958: . DOI:10.1167 PURPOSE. To compare visually guided manual prehension in participants with primarily central field loss (CFL) due to age-related macular degeneration and peripheral visual field loss (PFL) due to glaucoma. This study extends current literature by comparing directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Most of the patients in all three groups had difficulty in the distance and near visual activities, which is similar to the previous studies. [ 20 21 ] Myopia was found to be a more common refractive error when compared to a hyperopic error in all the groups, whereas hyperopic astigmatism was little more in OBV group when compared to the rest. The prevalence of refractive error among conditions causing central and peripheral field loss has not been studied in depth so far.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the patients in all three groups had difficulty in the distance and near visual activities, which is similar to the previous studies. [ 20 21 ] Myopia was found to be a more common refractive error when compared to a hyperopic error in all the groups, whereas hyperopic astigmatism was little more in OBV group when compared to the rest. The prevalence of refractive error among conditions causing central and peripheral field loss has not been studied in depth so far.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies based on self-reported functional ability to perform daily tasks indicate a weak correlation between task difficulty and VF defect severity in glaucoma patients [32,33]. Pardhan et al [29] observed that deficiencies in eye–hand coordination measured during reach–grasp–transport object tasks due to glaucoma were more strongly associated with central VF defects owing to age-related macular degeneration than peripheral VF defects. In contrast, Kotecha et al [28] postulated that VF defects in glaucoma are correlated with longer overall movements, reaching maximum speeds, and earlier deceleration during reaching-and-grasping.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, impairment was correlated with both increasing VF defect severity and impaired stereoacuity. Pardhan et al [29] studied the reach-to-grasp and transport-to-place tasks used to accurately move an object to a new location and found that patients with glaucoma made more errors compared to the control group. However, no significant differences ( p > 0.05) were observed between glaucoma patients and the control group in other phases of kinematic movement.…”
Section: Introductionmentioning
confidence: 99%
“…Shahina et al [13] states that patients with CFL will have more difficulty in grasping and reaching for an object when compared to patients with PFL. Similarly this study also reports that patients with CFL had more difficutly for near and intermediate visual tasks when compared to PFL group.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Although there are various studies which have investigated the use of low vision devices in different ethnic populations or different ocular conditions, still there is lack of information regarding the preference of LVD with regard to type of field loss. Literatures have compared many visual functions among people with central field loss and peripheral field loss, [3,[12][13][14] approval was obtained to analyze the hospital-based data and the tenets of Helsinki were followed.…”
Section: Most Conditions That Cause Low Vision Impact Either the Perimentioning
confidence: 99%